Main risk factors for lower limb amputation in patients with diabetic foot: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main risk factors for lower limb amputation in patients with diabetic foot. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “limb amputation”, “secondary amputation”, “repeat amputation”, “diabetic foot” and “neuropathy”. Full texts, available in Portuguese, English or Spanish, published between January 2016 and December 2021 were included; studies that focused on factors associated with lower limb amputation in patients with diabetic foot; studies that included diabetic patients over 18 years of age; studies whose factors were listed using statistical data. Results: 12 articles made up the final sample of this study, with a higher frequency of publication in 2021 (n: 04). Most of the studies used the retrospective cohort study, with a moderate level of evidence (III). It was found that the main risk factors statistically associated with the occurrence of lower limb amputation in diabetics were: hypertension (n: 06); peripheral neuropathy (n: 06); chronic kidney disease (n: 05); male sex (n: 05); smoking (n: 05); age over 60 years (n: 04); peripheral vascular disease (n: 04); presence of previous amputation, previous ulcer or foot deformities (n: 04); ulcer size (n: 03); diabetic retinopathy (n: 03). Conclusion: It was found that several factors may be involved in the increase in the prevalence of lower limb amputation in diabetic patients, from sociodemographic issues, lifestyle and factors related to the diabetes clinic itself. Prevention and early intervention actions that consider the reduction of these events are necessary.